Ways to Write Off the Cost of Inventory - Bahodirovna, Abdusalomova Nadira; A., Abduganiyev M. (Research Parks Publishers, 2023)
In this article, the influence of the applied methods of writing off inventories on the value of their balance and the consumption of materials in the accounting of materials at the enterprise has been studied. Using practical examples and related findings, we illustrate the impact on financial statements of applying the weighted average cost and first-to-stock (FIFO) methods used in material valuation.